Filling Treatment of Surface Subsidence Resulted From Underground Mining in a High-Altitude Mine - Deng, Daiqiang; Cao, Guodong; Liang, Yihua (Frontiers in Materials, 2021)
In the process of filling the goaf of Huashugou copper mine, the filling aggregate was the mine’s self-produced copper flotation tailings. The physical and chemical property tests showed that the tailings were relatively fine, and the cumulative contents of the 7.5, 15, 80, and 90 μm particles were 56.99%, 79.46%, 99.88%, and 100%, respectively. PSA42.5 Portland slag cement was selected as the cementing material for the tests. The amount of finely ground blast furnace slag added to the cement was 20–50%. The filling test blocks of all proportions were demolded within 24–36 hours, and the integrity of the formed filling bodies was satisfactory. Among them, the uniaxial compressive strength of the test block formed by the filling slurry with a tailings-to-cement ratio of 3/1 and a concentration of 74% after 3, 7, 28, and 60 days reached 0.833, 2.026, 4.520, and 6.560 MPa, respectively. The strengths of the other filling blocks also met the engineering design requirements. Based on the statistical regression analysis method, the influences of the slag cement content ꭓ₁ and the tailings water content ꭓ₂ on the filling body’s strength Ϭ were analyzed. The regression calculation also considered the interaction between ꭓ₁ and ꭓ₂, and the obtained multiple nonlinear regression model successfully predicted Ϭ. In production and application, the large density of tailings would accelerate their settling, which could easily cause blockage during the transportation of filling slurry through the pipeline. Regarding a series of existing filling materials and technical conditions, the filling process investigated in this study overcomes several unfavorable conditions. Using advanced and reliable technology and an industrial filling pump with a delivery pressure of 10 MPa, the prepared filling slurry concentration was 68–72% and the flow rate was 56–79 m₃/h. The tailings and PSA42.5 Portland slag cement combined quite well. The filling body in the goaf demonstrated excellent homogeneity, and the various industrial indicators met the technical requirements for mining deposits. The preparation of high-quality filling materials with a smooth filling process has played a positive role in the prevention and treatment of surface mountain cracks and collapse during underground mining in high-altitude areas.